I SPEAK BETTER ENGLISH: TEACHERS’ EXPERIENCES TOWARDS STUDENTS’ ATTITUDE IN SPEAKING THE LANGUAGE - Dave Aiken T. Ondes; Stephanie Shane C. Leornas, Rud-gie G. Paculanang, Mark Dave D. Gatera, Johana U. Caka, MAELT (CV. ADIBA AISHA AMIRA, 2023)
This study used qualitative research design and a phenomenological approach. The participants of this study were five English Teachers teaching in the parameters of Parang, Maguindanao, BARMM, Philippines. The researchers used a semi-structured in- depth interview in this study. The findings of this study revealed the experiences of the teachers toward students’ attitudes toward speaking the language. The study shows the behavior and performance of the students: fear and anxiety in speaking English; poor English speaking skills; the effect of social media; poor grammar in English sentence construction; discouragement caused by unfair judgment; use of jokes to skip English recitation; motivation and encouragement; providing opportunities and differentiated instructional activities. In addition, it also revealed the teachers’ teaching methods and coping strategies regarding the students’ issues with speaking the language. The participants made recommendations and coping strategies based on their personal experiences and challenges in order to create a program that would inspire and motivate them to improve their speaking skills.